Guerra e paz entre os Maxakali: devir histórico e violência como substrato da pertença - Ribeiro, Rodrigo Barbosa (2008)
This doctoral thesis analyses historical transformation and violence among the Maxakali people, whose language is classified as belonged to the branch of the Macro-Gê language family. Not too long ago, the Maxakalis used to live togheter in T I. Maxakali, situated in Bertópolis and Santa Helena de Minas, municipal districits located in the boundary between the state of Minas Gerais and the state of Bahia. Nevertheless, between 2003 and 2005 a violent conflict happened and, as a result, many people were murdered and part of the population was expelled from the territory. This scenario grabbed the attention to the necessity of understanding how the Maxakali people make this conflict part of their social life, associating the extreme forms of violence to some of the destructive manifestations which emerge from their social life. Attached to this objective, I carried out fieldwork between 2004 and 2007. Furthermore, I did a bibliographic research that could make me develop an approach to this phenomenon. By the end of this research, It is my conviction that the Maxakali people´s social life disposes of constitutive processes through the instauration of mechanisms of modification, which can assume some violent features. Thus, it is observed that both public wars and quotidian conflicts (such as, domestic conflicts) dispose of practices able to reformulate great part of Maxakali culture against the articulation of this mechanism in the symbolic system built by their myths and rituals. Thus, the aspects related to a certain type of anthropology, which privileges historical permanencies projecting these values in the concrete society analysed by them, even when everything indicates the inverse are not able to analyse the complex multifaceted sociopolitical horizon of the Maxakalis people. In order to measure this universe carefully, we needed to propose an approach open and plural, which could incorporate effectively controversial phenomena into the analyses, without reducing the explanation of these phenomena